2008
DOI: 10.2174/138920108785161505
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Biology of Jatropha curcas: A Mini Review

Abstract: Jatropha curcas is a drought resistant, perennial plant that grows even in the marginal and poor soil. Raising Jatropha is easy. It keeps producing seeds for many years. In the recent years, Jatropha has become famous primarily for the production of biodiesel; besides this it has several medicinal applications, too. Most parts of this plant are used for the treatment of various human and veterinary ailments. The white latex serves as a disinfectant in mouth infections in children. The latex of Jatropha contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
64
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 0 publications
4
64
0
3
Order By: Relevance
“…It is also used externally against skin diseases, piles and sores among the domestic livestock. The leaves of J. curcas also contain apigenin, vitexin and isovitexin which along with other factors enable them to be used against malaria, rheumatic and muscular pains (Thomas et al, 2008). Antibiotic activity of Jatropha has been observed against organisms including Staphylococcus aureus and Escherichia coli (Matsuse et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It is also used externally against skin diseases, piles and sores among the domestic livestock. The leaves of J. curcas also contain apigenin, vitexin and isovitexin which along with other factors enable them to be used against malaria, rheumatic and muscular pains (Thomas et al, 2008). Antibiotic activity of Jatropha has been observed against organisms including Staphylococcus aureus and Escherichia coli (Matsuse et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological and physiological applicability of latex production remain largely unknown. Numerous studies are underway to elucidate the morphological, biochemical and agronomic aspects in order to maximize the potential of this species (Laviola et al, 2015;Bhering et al 2013;Veronesi et al 2012;Behera et al 2010), such as using latex as product with medicinal applications (Katagi et al 2016;Costa et al 2014;Thomas et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to popular use, studies have shown that physic nut latex exhibits anticoagulant activity (Osonlyi and Anajobi 2003). Moreover, phytochemical analyses demonstrate that the latex of this species contains natural components with cytotoxic potential, including curcacyclins A and B (Insanu et al 2012) and curcusomes A, B, C and D (Aiyelaagbe et al 2011); anticancerous compounds, such as the protein curcin (JaramilloQuintero et al 2015) and the alkaloids jatrophine and jatropham (Thomas et al 2008); and antibactericidal and antimalarial compounds, such as curcacyclins A and B and jatrophidin (Sabandar et al 2013). Thus, extraction of these latex biocompounds would add commercial value to this cultivar, which could be used to produce biodiesel and drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The white latex serves as a disinfectant in mouth infections in children. The leaves of J. curcas also contain apigenin, vitexin and isovitexin, which, along with other factors enable them to be used against malaria, rheumatic and muscular pains [18]. Antibiotic activity of Jatropha has been observed against organisms including S. aureus and E. coli [8].…”
Section: Introductionmentioning
confidence: 99%